PENGARUH MODIFIKASI BURITAN SPEED BOAT TERUBUK EXPRESS 6 TERHADAP KECEPATAN KAPAL - Edy Haryanto (POLITEKNIK NEGERI BENGKALIS, 2018)
Speedboat Terubuk Express is a fast ship that is used as a means of sea transportation to carry passengers with a capacity of 60 people. Because it continues to experience losses, currently the Terubuk Express speedboat is modified by adding capacity and replacing the main drive engine which previously used an outboard engine with 4 x 200 horse power replaced with an internal engine that uses diesel fuel with power 1140 kilowatt. This study aims to determine the effect of stern shape changes and interaction total resistance before and after being modified on the hull to the speed of the ship.In this study several stages were carried out, namely a field survey to obtain the effect of size addition, making a model using Maxsurf 13.0 software, input data and running simulations using Hullspeed 13.01 then analyzing the results which included obstacles and speed.Based on the results of the analysis and calculations showed that the change in stern shape on the express speed boat speed caused L / B to increase by 1.2%, an increase in the comparison of the L / B value could affect the ability of the boat's motion and stability. The total resistance of the ship increased by 1.05% which at a speed of 35 knots before the change in total resistance was 33.5 kN while after the change in the total resistance became 35, 1 kN. Changes to the installed power engine can give a maximum speed of 49 knots with a total barrier of 47.5 kN. Increased speed greatly affects the engine seat and the strength of construction and the location of the longitudinal of bouyancy.